ANALISIS STRATEGI PEMASARAN DAN PELAYANAN DALAM UPAYA PENINGKATAN KUALITAS DAYA SAING BIRO PERJALANAN HAJI DAN UMROH PROSPEKTIF EKONOMI SYARI’AH (Studi Pada PT. Makkah Multazam Safir dan Al Madinah) - Nasrun Nazaruddin; Rahmat Hidayat; Ricco Andreas (Nizham Jurnal Studi Keislaman, 2020)
Hajj becomes part of the fifth pillar of faith after the creed, prayer, fasting, and alms. Hajj and Umrah are required for those who are powerful (capable), each man or woman once in a lifetime. In general, the Indonesian Muslim community performs the Hajj and Umrah to the Grand Mosque in Makkah through Hajj and Umrah travel. The number of devotees of Umrah pilgrims in Indonesia is so much the main attraction for entrepreneurs in the field of travel. This study uses a qualitative approach and is a type of field research (Field Research) and compares the pilgrimage and umrah services of PT. Makkah Multazam Safir and Al-Madinah Tour & Travel in Bandar Lampung which together are business entities that provide services or providers of Hajj and Umrah pilgrimage services in Baitullah. Two different data presentations will provide us with valid information regarding a program and services offered to prospective pilgrims in need. From the analysis that will be done will minimize errors in the future.